Evaluation of state-of-the-art hardware architectures for fast cone-beam CT reconstruction - Scherl, Holger; SpringerLink (Online service). (Wiesbaden Vieweg+Teubner, 2011)
This book considers the field of computed tomography including a review of state-of-the-art reconstruction algorithms and a concise assessment of the most recent hardware architectures. Holger Scherl introduces the reader to the reconstruction problem in computed tomography and its major scientific challenges that range from computational efficiency to the fulfillment of Tuy's sufficiency condition. The assessed hardware architectures include multi- and many-core systems, cell broadband engine architecture, graphics processing units, and field programmable gate arrays. The author focuses on the interplay between these recent hardware platforms and modern computed tomography reconstruction algorithms.
Electronic reproduction.
Keywords: Tomography -- Data processing; Three-dimensional imaging in medicine; Electronic books